Routine Screening for Fetal Limb Abnormalities in the First Trimester - Akhtar Hussain Phul, Kanzeez Fatima, Kalilash Kumar Daseja, Naimatullah Bozdar, Inayatullah Memon, Imran Khan Memon (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To evaluate the routine screening for fetal limb abnormalities in the first trimester. Study Design: Prospective study Place and Duration of Study: Department of Radiology and Department of Obstetrics & Gynaecology, Khirpur Medical College, Khairpur Mir’s from 1st October 2020 to 30th September 2022. Methodology: The study enrolled all pregnant women in visiting the Gynaecology OPD for routine check-up. All the cases were referred to ultrasound diagnostic for screening of fetal limb abnormalities. The total sample size of the study was assigned as 1000 fetuses from 980 women as 10 women had twin pregnancies. Limb reduction shortcomings included transverse-limb reduction deficit as well as longitudinal-limb reduction deficit as seen through absent radius and also club hand, absent fibula phocomelia. The diagnosis of the limb shortening was based on the length of long bone if <5th percentile. Lethal skeletal dysplasia suspicion was based on narrow thorax and long bone abnormalities. Results: The mean age of the pregnant women was 27.6±5.3 year. Around 26% of the women were nulliparous. The fetal limb anomaly was presented in 0.9% of the total cases. Within these, 0.7% was those women with single fetus while 0.2% had twin pregnancy. There were 60% of the women who were identified with fetal anomaly on their first screening visit within 1st trimester transverse limb anomaly was observed in 2 case within first trimester whereas 2 cases of club foot were identified in first trimester and one in third trimester. Conclusion: The fetal limb anomaly can be feasibly screened within first trimester. It has a prevalence of 0.9% with transverse limb deficiencies and club foot to be presented in highest frequency. Keywords: Fetal limb abnormalities, First trimester, Prevalence